Adorno’s Negative Dialectics with Bataille: Poisoning the Absolute - Austin, Matthew James (Strategies of Critique, 2008)
My paper has two basic aims: Primarily, I illustrate Theodor Adorno’s critique of Hegelian ‘totality.’ Secondarily, I outline a connection between the thought of Adorno and Georges Bataille. Briefly stated, I explore how the efforts of both thinkers “recommence and undo Hegel’s Phenomenology,” to borrow a line from Bataille. My paper has three basic moves. First, I outline the problem of ‘totality,’ or why the ‘Whole is false.’ Second, I outline the means of totality’s disruption, or how totality poisons itself. Here, Bataille offers his poisonous services as I explore the usefulness of that which is wholly without use to Hegel: abstract negativity. And finally, I outline Adorno’s constructive analytic solution to the ‘fallacy of constitutive subjectivity’ in the form of the constellation.